Personal protective equipment as a measure to limit disability among ironworkers in maros regency - A.Fachrin, Suharni; Baharuddin, Alfina; Jama, Fatma; Ratu Purnama, Hukma; Yuliati, Yuliati; Andayanie, Ella (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2025)
Amidst the onslaught of modernization, traditional handicrafts still hold a unique appeal. One such craft is blacksmithing. Blacksmiths, despite their high level of skill in producing handicrafts, often face serious health and safety risks due to exposure to burning, heavy equipment use, and direct contact with hazardous materials. Observations at the partner site revealed workplace accidents such as burns (35.8%), contact with hot iron (58.7%), and being struck by iron materials (35%) due to the nature of their work. Based on these issues, community service activities were conducted in the form of education on the use of personal protective equipment (PPE) as an effort to limit disabilities among iron craftsmen. The results of the education on the benefits of PPE showed an increase in knowledge, attitude, and behavior, with pre-test results of 65%, 77%, and 85%, respectively, and post-test results of 83%, 89%, and 91%, respectively. In the results of the education on the benefits of fire extinguishers, there was an increase in knowledge, attitude, and behavior, with pre-test results of 75%, 80%, and 85%, respectively, and post-test results of 88%, 83%, and 90%, respectively. It can be concluded that the effectiveness of this community service program was successful